2015
DOI: 10.1371/journal.pone.0123833
|View full text |Cite
|
Sign up to set email alerts
|

532 nm Low-Power Laser Irradiation Facilitates the Migration of GABAergic Neural Stem/Progenitor Cells in Mouse Neocortex

Abstract: Background and ObjectiveAccumulating evidence has shown that low-power laser irradiation (LLI) affects cell proliferation and survival, but little is known about LLI effects on neural stem/progenitor cells (NSPCs). Here we investigate whether transcranial 532 nm LLI affects NSPCs in adult murine neocortex and in neurospheres from embryonic mice.Study Design/Materials and MethodsWe applied 532 nm LLI (Nd:YVO4, CW, 60 mW) on neocortical surface via cranium in adult mice and on cultured cells from embryonic mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Although this approach facilitated the estimation of the proliferation and differentiation of NPCs, it provided only indirect evidence of neuroblast migration. The signs of migration can be: a distribution pattern of migrating neuroblasts (markers – DCX and sometimes PSA-NCAM) from the place of origin toward the place of destination (Palma-Tortosa et al, 2017), a density gradient of neuroblasts with high density at the presumed place of origin (Thored et al, 2006; Fukuzaki et al, 2015), as well as the change in this gradient at subsequent time points (Yan et al, 2007; Oya et al, 2009; Li et al, 2011). Also, in their works researchers pay due attention to the orientation of migrating cells.…”
Section: Methods For Studying the Production And Migration Of Npcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this approach facilitated the estimation of the proliferation and differentiation of NPCs, it provided only indirect evidence of neuroblast migration. The signs of migration can be: a distribution pattern of migrating neuroblasts (markers – DCX and sometimes PSA-NCAM) from the place of origin toward the place of destination (Palma-Tortosa et al, 2017), a density gradient of neuroblasts with high density at the presumed place of origin (Thored et al, 2006; Fukuzaki et al, 2015), as well as the change in this gradient at subsequent time points (Yan et al, 2007; Oya et al, 2009; Li et al, 2011). Also, in their works researchers pay due attention to the orientation of migrating cells.…”
Section: Methods For Studying the Production And Migration Of Npcsmentioning
confidence: 99%
“…At the same time, some studies do in fact suggest that the production of new neurons can occur in the injured cortex (Gu et al, 2000; Kuge et al, 2009; Ohira et al, 2010; Shimada et al, 2010, 2012; Bi et al, 2011; Nakagomi et al, 2011, 2015; Fukuzaki et al, 2015). Bi et al (2011) showed by special labeling that, after neonatal hypoxia, cortex astrocytes in neonates gain the properties of NSCs and differentiate into new neurons both in the damaged cortex and after having been translated into cell culture.…”
Section: Neurogenesis In the Injured Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, notable enhancements in brain functions have been achieved using 1064 nm Nd:YAG laser light which has high penetration ability through the skull [210,202]. Increases in neuronal proliferation and ATP production have been found following green laser irradiation (532 nm) [215,216], and promotion of differentiation and proliferation of stem cells following irradiation with blue LED (420 nm) and green light (540 nm) [217] have been also shown. The activation of transducing cellular signals through the several intermediates following the absorption of blue and green light by cryptochromes and opsin photoreceptors, respectively, has been explained as mechanism involved in photostimulatory effects of this range of wavelengths (Fig.…”
Section: Influence Of Irradiation Parameters In Brain Pbm Therapymentioning
confidence: 99%
“…Different modalities of photobiomodulation have been employed as adjuvant treatments for bone loss, myalgia, skin burns, spinal cord injury, and pulp repair [6][7][8][9][10]. Clinical and laboratory studi es have evaluat ed the eff ect of photobiomodulation on the healing of different tissues, such as the muscle and cartilage [11,12], neuronal cells [13,14], bone [15,16], and the dentin-pulp complex [2,17,18].…”
Section: Introductionmentioning
confidence: 99%